2007
DOI: 10.1016/j.snb.2006.04.097
|View full text |Cite
|
Sign up to set email alerts
|

Capture of airborne nanoparticles in swirling flows using non-uniform electrostatic fields for bio-sensor applications

Abstract: Collection of biological particles is the first and critical step for any biological agent detection system. Towards our goal of capturing and detecting airborne biological entities in real time, here we investigate on the design of an electrostatic particle capture system. We report on the capture of airborne 100 nm diameter polystyrene nanoparticles as a model system, in swirling flows under non-uniform electrostatic fields with an electrospray aerosol generator and a homemade particle collector. The particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Particle generator, neutralizer and particle collector Figure 1 shows a schematic of a particle generation system and the particle collector (Jang et al 2007), and its top view, which shows the three different inlet/outlet configurations, FO (i), BO (ii) and SO (iii) (Jang et al 2006). This collector has five metal sheets (12 × 12 mm 2 ) on its bottom, acting as the positive electrodes to capture negatively charged airborne nanoparticles or microorganisms, and a large grounded electrode on the top (see figure 1(c)).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Particle generator, neutralizer and particle collector Figure 1 shows a schematic of a particle generation system and the particle collector (Jang et al 2007), and its top view, which shows the three different inlet/outlet configurations, FO (i), BO (ii) and SO (iii) (Jang et al 2006). This collector has five metal sheets (12 × 12 mm 2 ) on its bottom, acting as the positive electrodes to capture negatively charged airborne nanoparticles or microorganisms, and a large grounded electrode on the top (see figure 1(c)).…”
Section: Methodsmentioning
confidence: 99%
“…In the current simulation, both flow and electric fields were obtained separately and particles were traced from flow fields without considering the effects of electric fields on the particles. These particle tracks give important information on the relationship between the particle velocities, the distance from the electrodes to the particles and the captured particle counts with the electrode position when the electrostatic forces are almost constant with the electrode positions (Jang et al 2007). Particle trajectories in the collector were numerically computed with the discrete phase model of a CFD code FLUENT 6.2.…”
Section: Computation Of Particle Trajectories In the Collectormentioning
confidence: 99%
See 1 more Smart Citation
“…17 The current detection limit can be further improved by higher flow rates in combination with secondary amplification techniques such as gold nanoparticle conjugation 18 and/or the use of electric fields to attract the viruses. 16 In conclusion, we presented the capture of airborne Vaccinia viruses in real-time using a mass sensitive device. We showed that the capture rate of airborne viruses measured by a QCM was linear with virus concentrations and that it had the potential for quantitative detection of airborne viruses.…”
mentioning
confidence: 96%
“…The concentration of airborne viruses generated at the capillary tip of the aerosol generation system can be approximated by dividing the product of the concentration of the starting virus suspension in fluid ͑viral particles/ml͒ and the suspension feed rate ͑432 nl/ min͒ by the gas mixture flow rate ͑l/min͒. 16 Considering that only a small fraction of the particles ͑ϳ9.5% ͒ out of those generated at the capillary tip can reach the QCM crystal, 16 the minimum detectable airborne virus concentrations over the quartz crystal are calculated as around 40 and 210 particles/ ml at a flow rate of 2.0 and 1.1 l / min, respectively, which are close to the detection limit ͑10 particles/ ml͒ by BAMS. 17 The current detection limit can be further improved by higher flow rates in combination with secondary amplification techniques such as gold nanoparticle conjugation 18 and/or the use of electric fields to attract the viruses.…”
mentioning
confidence: 99%